Interpretable machine learning for optimization of ultrasound-assisted polysaccharide extraction using natural deep eutectic solvents: From yield enhancement to structural and antioxidant activity validation - Shulu Zhang; Jingting Han; Ruichen Gao; Yeqing Xu; Zheng Feng; Xinhui Huang; Yinze Zhong; Qingxia Wang; Xinran Yu; Siyu Chang; Meiting Jiang; Zhibin Wang; et al. (Bioresource Technology, 2026)

The algebraic deduction method (ADM) for contact detection of rock blocks: a time-continuous strategy beyond time-intermittent contact detection - Ruichen Zhang; Jun Zheng; Zheqi Tian; Cunbao Li; Shigui Du (International Journal of Rock Mechanics and Mining Sciences, 2026)

IS-RPB-intensified resource utilization of coal fly ash coupled with multidimensional techno-economic and life cycle assessment - Zhiguo Yuan; Zhong Guo; Chunge Dang; Shuli Zhang; Youzhi Liu; Ruichen Wang (Process Safety and Environmental Protection, 2026)

Cluster analysis of rock block shapes: A novel quantitative method for characterising rock mass structures - Zheqi Tian; Jun Zheng; Ruichen Zhang; Rafael Jimenez; Dongpo Wang; Jiongchao Wang (Computers and Geotechnics, 2026)

High entropy alloy PtRuCuCoNi nanosponges with tunable electronic configurations for electrocatalytic lactic acid oxidation toward upcycling waste polylactic acid - Bingshuo Li; Xiaokun Fa; Ruichen Geng; Liuyang Jiang; Ruiping Liu; Zhihan Zhang; Yinglong Wang; Shuli Yin (Chemical Engineering Journal, 2026)

Personalized thermal comfort elicitation for human-centric building environments with low-cognitive-load conversational AI - Yizheng Li; Huan Zhao; Guandong Su; Yang Meng; Yongan Zhang; Yan Li; Ruichen Ding; Zhangxing Chen; Jinyue Yan (Building and Environment, 2026)

Sub-2 nm ultrafine high-entropy alloy nanowires with multi-atom catalytic sites for efficient electrocatalytic upcycling of waste plastics - Xiaokun Fa; Ruichen Geng; Zhihan Zhang; Yinglong Wang; Fengbin Zheng; Shuli Yin (Chemical Engineering Journal, 2026)

Dataset of China Kuroshio Extension Observatory (CKEO): Moored Buoy Observations in the Kuroshio–Oyashio Transition Zone - Zhaohui Chen; Yueqi Zhang; Ruichen Zhu; Zhongxiang Fan; Jia-Zhen Wang; Xin Ma; Guoqing Ren; Haiyuan Yang; Lixiao Xu; Xiaopei Lin; Lixin Wu (Advances in Atmospheric Sciences, 2026)
The Kuroshio–Oyashio Transition Zone (KOTZ) serves as a vital dynamic interface between the warm Kuroshio Extension and the cold Oyashio Current. However, severe sea conditions with strong ocean currents, winds and waves pose challenges for sustained in situ observations of both oceanic and atmospheric variables. This paper introduces the China Kuroshio Extension Observatory (CKEO), a moored observatory program designed for long-term observations in the KOTZ. We provide a dataset of meteorological and oceanographic properties, including sea surface wind, air temperature, atmospheric pressure, relative humidity, sea surface temperature, sea surface salinity, ocean currents in the upper 100 m, and temperature profile in the upper 500 m. The CKEO, which began operations in 2019, provides a continuous air–sea observational dataset of the KOTZ to the scientific community and advances the understanding of multiscale physical processes in this region.

Postharvest application of plasma-activated water to extend shelf life of strawberries - Yingman Gao; Yupan Zhu; Panfeng Guan; Leiyi Zhang; Xinyue Li; Guihuan Wei; Chenbin Hu; Ruichen Sha; Nanshan Du; Ruonan Ma; Zhen Jiao; Bing Li (Food Chemistry, 2026)

Thermo-responsive co-delivery of therapeutic drug and Gasotransmitter for treating atherosclerosis - Yinhong Xie; Mengchen Chi; Ruichen Dong; Qiong Hu; Zheng Zeng; Lingting Fan; Yaolei Zhang; Hongyu Sun; Yonghong Fan; Yajun Weng (Chemical Engineering Journal, 2026)

Femtosecond laser-fabricated defect-rich PtRe alloy clusters for enhanced alkaline hydrogen evolution - Xianze Zhang; Junwen Xiong; Zhiyi Sun; Ruichen Lu; Zikang Su; Chen Zhang; Qimiao Zhu; Shilong Yuan; Lan Jiang; Shengjie Xia; Liquan Sun; Xingdong Wang; et al. (Chemical Engineering Journal, 2026)

Succession patterns, environmental connections, and assembly mechanisms of gut microbiota in the giant freshwater prawn (Macrobrachium rosenbergii) across lifespan - Songbao Zou; Yao Zheng; Julin Yuan; Meng Ni; Mei Liu; Dan Zhou; Qiang Gao; Mingfeng Deng; Ruichen Wang; Xin Zhang (Aquaculture, 2026)

Electron-delocalization across high-entropy alloy nanofibers for efficient electrocatalytic glycerol oxidation - Yaxuan Li; Zhihan Zhang; Ranran Wei; Xiaoying Zhang; Ruichen Geng; Fengbin Zheng; Liang Wang; Yinglong Wang; Shuli Yin (Chemical Engineering Journal, 2026)

In situ growth of ultrasmall MoO3 nanoparticles into 3D porous reduced graphene oxide for efficient oxidative desulfurization of high-sulfur - Peng Zuo; Xianping Chu; Fanfan Liu; Xu Cai; Ruichen Li; Yanbo Sun; Zhouqin Xu; Zhiwei Zhang; Yun Shen; Jinyun Liu; Yefeng Liu (Journal of Environmental Chemical Engineering, 2025)

Preparation and tribological investigation of self-lubricating epoxy composite containing hollow mesoporous silicon nanocapsules loaded with PAO6/Cu nano-oil - Ruichen Zhang; Luyao Wang; Chunjian Duan; Shengmao Zhang; Liyong Niu; Pingyu Zhang; Zhijun Zhang; Seeram Ramakrishna; Chuanping Gao (Chemical Engineering Journal, 2025)

Upcycling PET waste into carbon quantum dots as flame retardant of PET for closed-loop recycling - Jianfei Wei; Guocong Ma; Yaoyao Tang; Jing Zhang; Gaoling Jin; Chaohui Ma; Linhan Bing; Zhiguo Zhu; Zhenfeng Dong; Puzhen He; Ruichen Zhou; Rui Wang; et al. (Chemical Engineering Journal, 2025)

Global sustainable pathway for lithium metal production: A critical review and best practice guide - Ruichen Wang; Yuexin Han; Yanjun Li; Feilong Zhang; Chunge Dang; Zhiguo Yuan; Jie Liu (Chemical Engineering Journal, 2025)

A small block treatment method in three-dimensional block identification for rock block system mechanical analysis - Zheqi Tian; Jun Zheng; Ruichen Zhang; Qing Lü; Shengkui Tan; Junfeng Li (Computers and Geotechnics, 2025)

Self-templated fabrication of heterogeneous F doped NiCo-alkoxides/NiCo hydroxides yolk-shelled spheres with enhanced performance for supercapacitors - Xu Zhang; Ying Chen; Shuxian Song; Lu Song; Ruichen Zhai; Yulan Meng; Shaojie Li; Lijuan Wei; Xutong Yang; Anmin Liu (Chemical Engineering Journal, 2025)

Transparent wood electrode for electrocatalysis: Preparation, micro/nano structures fabrication, functionalization and applications - Yurui Huang; Xianze Zhang; Linxiang Li; Ruichen Lu; Xueqiang Zhang (Chemical Engineering Journal, 2025)

Oil Spill Occurrence and Pollution Risk Assessment Based on Sea State, Oil Platform Location, and Shipping Route Density in the Bohai Sea - Tao Liu; Ruichen Cao; Minxia Zhang; Xing Chen; Fan Bi; Jiangling Xu (Journal of Marine Science and Engineering, 2025)
The Bohai Sea is the only semi-enclosed inland sea in China. With active marine economic activities, it faces a persistently high risk of oil spill accidents. This study assesses the occurrence risk and pollution risk of oil spills by considering factors such as sea state, the location of oil platform, and shipping route density in the Bohai Sea. The results show that the central part of the Bohai Sea, the southern Liaodong Peninsula, and the Bohai Strait area have a relatively high occurrence risk of oil spills due to busy maritime traffic and harsh sea conditions. In contrast, some areas in the northern, western, and southern parts of the Bohai Sea have a relatively low occurrence risk of oil spills because of weak maritime activity intensity and relatively calm sea state. In terms of the oil pollution risk, its distribution in the Bohai Sea shows significant seasonal characteristics, which are mainly comprehensively affected by multiple dynamic factors such as circulation, monsoon, and seawater exchange. Based on the oil pollution risk distribution, seasonally targeted strategies are proposed, which can provide a scientific basis for oil spill prevention and emergency management in the Bohai Sea, and help relevant departments formulate targeted prevention and control strategies.

Sustainable domestic sewage treatment by a reinforced soil infiltration system: Dual emphasis on pollutants and greenhouse gases - Ruichen Wang; Shuli Zhang; Hongquan Wei; Mingxiao Zeng; Zhiguo Yuan; Chunge Dang (Chemical Engineering Journal, 2025)

Ecological and Evolutionary Factors Contribute to the Uneven Diversification of Firs in the Northern Hemisphere - Qiaoping Xiang; Jie Yang; David S. Gernandt; Tongxin Ye; Ling Yang; Jiaming Pan; Ruichen Xiang; Cheng Zhao; Koh Nakamura; Xianchun Zhang; Yongbo Liu; Ran Wei (Journal of Biogeography, 2025)
Aim The Northern Hemisphere harbours the greatest diversity of temperate plants on Earth, with East Asia having the highest species richness compared with North America and Europe. When and how this uneven diversification pattern emerged remains unclear. Here, we use a conifer genus that forms extensive forests in the Northern Hemisphere to explore a fundamental question in ecology and evolution: what processes underlie temperate biodiversity through time and space? Location The Northern Hemisphere. Taxon Abies . Methods To reconstruct a well‐supported framework for estimating diversification rate, we performed phylogenetic analyses using concatenation and coalescent methods based on 58 fir taxa and 56 nuclear single‐copy genes. Niche evolution was explored using species occurrence data and environmental factors based on the l1ou model. Multiple regression was carried out to identify correlations between species richness and environmental variables at global and regional scales, to evaluate factors of species diversity preference, and potentially to explain the evolutionary history of firs. Results We identified East Asia as having the highest species diversity and speciation rate. Two clade‐specific niche shifts corresponding with the distribution of firs were detected, one in the Himalaya‐Hengduan Mountains ( c. 12.2 Ma) and the other in the Mexican highlands ( c. 14.3 Ma), but none in the Euro‐Mediterranean region. Fir species richness increased with cool temperatures both globally and regionally. Seasonal precipitation showed significant positive correlation to species richness on a global scale and in North America and the Euro‐Mediterranean region. Soil factors showed significant trends and moderate correlations with species richness in the Himalaya‐Hengduan Mountains and Mexican highlands. Main Conclusions Our results indicate that modern firs prefer cool climates with seasonal rainfall. East Asian firs experienced niche shifts with the Himalayan orogeny in the Middle Miocene. Novel heterogeneous habitats due to changes in topography and the establishment of a monsoon climate, accompanied by niche shift, can account for the high speciation of firs in East Asia. A similar process is found in the Mexican highland firs. In contrast, cold–dry continental climate in North America since the late Paleogene and the lack of seasonal rainfall and relatively stable topography in the Euro‐Mediterranean region are the main limiting factors for fir diversification. Our study rejects the ‘clade age’ hypothesis but supports the hypothesis that niche shift related to high diversification rate triggered by environmental heterogeneity underlies the uneven species diversity of the Northern Hemisphere.

Interaction and bacterial effects of microplastics pollution on heavy metals in hyporheic sediments of different land-use types in the Beiluo River Basin - Bingjie Li; Zeyu Chen; Yuting Zhang; Ruichen Mao; Jinxi Song; Yongqing Long; Bin Tang; Jiayuan Feng; Myint Myint Nyein (Environmental Pollution, 2025)

Techno-economic-environmental analysis based on life cycle carbon accounting and pollutants audit for cleaner production of electrolytic manganese - Ruichen Wang; Shuli Zhang; Yajing Guo; Jingyang Liu; Feilong Zhang; Chunge Dang (Process Safety and Environmental Protection, 2024)

Genomic selection on ear height, plant height and grain yield in the primary testing stage of maize hybrids - Xinying Kong; Shuwen Ji; Yubo Liu; Xuecai Zhang; Meiling Liu; Chen Yue; Ruichen Yang; Cong Li; Xiaomei Dong; Ao Zhang; Yanye Ruan (Euphytica, 2024)

Temporal and spatial variations in squid jigging catch efficiency in the Oyashio Extension region - Zixuan Niu; Zhaohui Chen; Wei Yu; Haihong Guo; Ruichen Zhu; Xiaoyi Zhang (Fisheries Oceanography, 2024)
The abundance of fishery resources significantly impacts the ratio of fishing effort to harvest. However, traditional statistics of fishery catches or commonly used catch per unit effort (CPUE) metrics cannot accurately capture the complexity of resource abundance in the ocean. To address this issue, we propose here a novel approach that integrates the actual fishery catch from vessel logs with fishing duration obtained through automatic identification system (AIS) positioning. This combined analysis eliminates confounding factors and introduces a novel metric called “catch efficiency (CE)” to evaluate fishing operations more accurately, thereby reflecting resource abundance in a more reasonable way. In this study, we focus on the CE of squid in the Oyashio Extension region in the Northwestern Pacific. Our analysis reveals significant temporal and spatial variations of CE, manifesting in both intensity and distribution patterns. Moreover, our findings establish a close relationship between CE and background water mass distribution, chlorophyll‐a concentration, and micronekton biomass. This implies that the resource abundance of squid can be inferred by considering the varying environmental factors within the fishing area.

Nomogram to predict central lymph node metastasis in papillary thyroid carcinoma - Dehui Qiao; Xian Deng; Ruichen Liang; Xu Li; Rongjia Zhang; Zhi Lei; Hui Yang; Xiangyu Zhou (Clinical & Experimental Metastasis, 2024)

Do small block treatments matter in block identification for rock block system mechanical analysis? - Zheqi Tian; Jun Zheng; Xiaochu Peng; Qing Lü; Ruichen Zhang; Xianchun Ma; Jianhui Deng (Computers and Geotechnics, 2024)

Research on scallop shells transport of the Yantai coastal region in the Bohai Sea - Le Chen; Yibo Zhang; Yongzhi Liu; Ruichen Cao; Xianqing Lv (Frontiers in Marine Science, 2024)
Introduction Bivalve aquaculture is an important pillar of China's fisheries, with over 1 million tonnes of scallop shells produced annually. However, most of these shells are directly discarded into the sea, leading to continuous pollution of the marine and coastal environments, especially the coast of Yantai in the Bohai Sea where a large number of discarded scallop shell have accumulated. Methods To trace the fate of scallop shells in the ocean, this study established a model for the transport of scallop shells, coupling a two-dimensional tidal current model using the adjoint method with a Lagrangian particle model. By simulating nested tidal models, the distribution of tidal residual current in the Yantai coastal region was obtained. Then, a Lagrangian particle model was used to track the transport pathways of pollutants in the sea. Results Driven by the residual current calculated from the tidal model with the actual situation, possible pollutant release areas were inferred. The results of Lagrangian particle tracking experiments indicate that pollutants were released from the upstream accumulation area, specifically the area near Penglai Hulushan, confirming previous speculation. Discussion The scallop shells transport model can accurately simulate the spatiotemporal profile of scallop shells, which is helpful for managing scallop shell resources and improving the level of shell reuse.

The competition of heavy metals between hyporheic sediments and microplastics of driving factors in the Beiluo River Basin - Bingjie Li; Ruichen Mao; Zeyu Chen; Yuting Zhang; Jinxi Song; Nan Li; Bin Tang; Jiayuan Feng; Mingchang Guan (Journal of Hazardous Materials, 2024)

Evaluating net primary productivity dynamics and their response to land-use change in the loess plateau after the 'Grain for Green' program - Ruichen Mao; Lutong Xing; Qiong Wu; Jinxi Song; Qi Li; Yongqing Long; Yuna Shi; Peng Huang; Qifang Zhang (Journal of Environmental Management, 2024)

Insectivorous birds are more sensitive to urban greenspace changes in Guangzhou city, China - Ruichen Wu; Qiang Zhang; Zezhou Hao; Le Li; Bingtao Gao; Jianrong Li; Xiaotian Liu; Chao Liao; Nancai Pei (Urban Forestry & Urban Greening, 2024)

Glacial debris flow susceptibility mapping based on combined models in the Parlung Tsangpo Basin, China - Yonghao Zhou; Xiewen Hu; Chuanjie Xi; Hong Wen; Xichao Cao; Tao Jin; Ruichen Zhou; Yu Zhang; Xueqiang Gong (Journal of Mountain Science, 2024)

With spatial distribution, risk evaluation of heavy metals and microplastics to emphasize the composite mechanism in hyporheic sediments of Beiluo River - Bingjie Li; Jinxi Song; Mingchang Guan; Zeyu Chen; Bin Tang; Yongqing Long; Ruichen Mao; Jiawei Zhao; Wenjin Xu; Yuting Zhang (Journal of Hazardous Materials, 2024)

DEHP and DBP, common phthalates, induce glucose metabolism disorders in rats via oxidative damage of PI3K/Akt/GLUT4 signaling - Liping Li; Lingyan Huang; Ruichen Lei; Pengju Zhang; Yi Yang; Herong Liu; Yuhong Zhang (Environmental Pollution, 2024)

Dynamic characteristics and erosion effect of a landslide-induced debris flow which occurred in Pingwu, southwest China - Bo Liu; Kun He; Xiewen Hu; Yufang Zhang; Kun Yuan; Jian Cui; Chuanjie Xi; Ruichen Zhou (Bulletin of Engineering Geology and the Environment, 2023)

Triclocarban exposure aggravates dextran sulfate sodium-induced colitis by deteriorating the gut barrier function and microbial community in mice - Mengyu Qin; Hehua Lei; Yuchen Song; Mengjing Wu; Chuan Chen; Zheng Cao; Cui Zhang; Ruichen Du; Ce Zhang; Xian Wang; Limin Zhang (Food and Chemical Toxicology, 2023)

Exogenous bile acids regulate energy metabolism and improve the health condition of farmed fish - Lei Wang; Gladstone Sagada; Chenyang Wang; Ruichen Liu; Qiang Li; Chen Zhang; Yunzhi Yan (Aquaculture, 2023)

Analytical Method for High-Precision Seabed Surface Modelling Combining B-Spline Functions and Fourier Series - Ruichen Zhang; Guojun Zhai; Shaofeng Bian; Houpu Li; Bing Ji (Marine Geodesy, 2022)

Prevention of acetaminophen-induced hepatocyte injury: JNK inhibition and GSTA1 involvement - Yicong Chang; Jingshan He; Bingke Ma; Muhammad Ishfaq; Jiaqi Wang; Ruichen Zhang; Liang Yuan; Jiarui Liu; Changwen Li; Fangping Liu (Molecular & Cellular Toxicology, 2021)

Effects of different habitats on the bacterial community composition in the water and sediments of Lake Taihu, China - Wenjie Chang; Jieli Sun; Yong Pang; Songhe Zhang; Lixue Gong; Jiaang Lu; Bin Feng; Ruichen Xu (Environmental Science and Pollution Research, 2020)

Araneose Ti3+ self-doping TiO2/SiO2 nanowires membrane for removal of aqueous MB under visible light irradiation - Zhao Gao; Hanpei Yang; Jingtao Mao; Li Kang; Ruichen Zhang; Siqi Chai; Junming Wu; Wei Li (Environmental Science and Pollution Research, 2020)